Chapter Architetture olivettiane: un itinerario da sud a nord - Piccinini, Mario (Firenze University Press, 2025)
Adriano‘s interest and passion for architecture and urban planning they manifest themselves both for industrial architecture, but also in the creation of residential neighborhoods for the employers of the Olivetti. The Neighborhoods of Ivrea are un example between 1930 and 1960. Ivrea, in 2018, was appointed from Unesco as World Heritage of Umanity. Among the most works is remembered la Summer colony of Massa Marittima (1948-1958). This work represent an example of insertion into the natural contest. Other examples are the Factory of Pozzuoli (1951-1954) an example of design which over looks the Gulf of Naples set in a garden resulting from a careful study. Regarding urban planning it is worth remembering il Piano Regolatore della valle D’Aosta del 1936-1937,coordinated by Adriano which represents in all respects a regional plan